Maintaining mitochondria in beige adipose tissue - Lu, Xiaodan (Adipocyte, 2019)
Individual cell types vary enormously in the amount of different organelles they contain. One such organelle is the mitochondrion. Understanding how mitochondrial levels are controlled is essential since so many disease states seem to involve mitochondrial function. The beige adipocyte is an inducible form of adipocyte that emerges in response to cold exposure and some other external stimuli. To perform its thermogenic function, its level of mitochondria increases dramatically. If the stimuli are removed the mitochondrial levels return to base line. Following the withdrawal of external stimuli, beige adipocytes directly acquire a white fat-like phenotype through mitophagy-mediated mitochondrial degradation. The beige cell is therefore a dynamic model for studying the mechanism of mitochondrial biogenesis and degradation.